Redescription of Mitodiplosis graminis (Diptera: Cecidomyiidae), a gall midge inhibiting the flowering of pyp grass Ehrharta villosa (Poaceae) in South Africa - Kolesik, Peter; Wood, Alan R. (Zootaxa, 2019)
Mitodiplosis graminis Kieffer, the only species of the genus Mitodiplosis (Diptera: Cecidomyiidae), was described in 1914 as the causative agent of an unspecified gall on pyp grass Ehrharta villosa (Poaceae) in South Africa. The type specimens are presumed lost. We reared all developmental stages of the gall midge, redescribe here the male and female, and describe for the first time the gall, egg, larva and the pupa. Diagnosis of the genus Mitodiplosis is extended. The gall is a large thickening of the stem that becomes malformed and does not produce flowers. Pyp grass is an environmental weed in Australia and New Zealand and M. graminis can potentially be used as a biological control agent. With a wing length of over 6 mm in some specimens, M. graminis is one of the largest species of Cecidomyiidae.